2009
DOI: 10.1111/j.1600-0781.2009.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ultraviolet erythema not suppressed by oral prednisolone: a randomized crossover study

Abstract: The threshold UV erythema suppression model assessed in this study could not distinguish between oral prednisolone and placebo. This UV-erythema suppression test system is not promising as a model to test the anti-inflammatory potency of systemic steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The role of systemic steroids in the suppression of the phototest response requires further study. While such an effect has been noted in the photosensitive skin diseases chronic actinic dermatitis and polymorphic light eruption [29], it seems not to be a feature of the normal ultraviolet skin responses assessed by phototesting [30]. …”
Section: Discussionmentioning
confidence: 98%
“…The role of systemic steroids in the suppression of the phototest response requires further study. While such an effect has been noted in the photosensitive skin diseases chronic actinic dermatitis and polymorphic light eruption [29], it seems not to be a feature of the normal ultraviolet skin responses assessed by phototesting [30]. …”
Section: Discussionmentioning
confidence: 98%
“…Since this first report, controlled trials have multiplied and similar drugs have been tested via systemic administration; however, they have had little apparent benefit to the subjects. For instance, a recent study demonstrated that 4 consecutive days of oral corticosteroid do not have any effect on erythema of irradiated skin [65]. These studies provide clear evidence that systemic use of corticosteroids is not an effective treatment to alleviate the symptoms of skin sunburn.…”
Section: Uvb-induced Hypersensitivity: Pharmacologymentioning
confidence: 98%
“…This case is of interest as he could have been labelled as having an exposed site contact dermatitis with ‘undiscovered allergen’ rather than the true diagnosis of CAD. This situation is different from that seen in normal subjects where prednisolone at a dose of 30 mg daily did not significantly inhibit the phototest erythema result 1 …”
mentioning
confidence: 99%